Pharmacological Treatment of Obesity in Children and Adolescents: Present and Future. (15th December 2010) - Iughetti, Lorenzo; China, Mariachiara; Berri, Rossella; Predieri, Barbara
Abstract : The prevalence of overweight and obesity is increasing in children and adolescents worldwide raising the question on the approach to this condition because of the potential morbidity, mortality, and economic tolls. Dietetic and behavioral treatments alone have only limited success; consequently, discussion on strategies for treating childhood and adolescent obesity has been promoted. Considering that our knowledge on the physiological systems regulating food intake and body weight is considerably increased, many studies have underlined the scientific and clinical relevance of potential treatments based on management of peripheral or central neuropeptides signals by drugs. In this paper, we analyze the data on the currently approved obesity pharmacological treatment suggesting the new potential drugs.